Vibration and modal analysis of a rotating disc using high-speed 3D digital image correlation. (15th April 2019) - Huňady, Róbert; Pavelka, Peter; Lengvarský, Pavol
Highlights: An effective method of measuring the vibration responses of a rotating structure using DIC is introduced. The basis of the method is a numerical elimination of rigid body motions. No additional devices or modifications of the measuring system are required. The results of operating deflection shape analysis, operational modal analysis and run-up analysis are presented. It is proven that the proposed method provides higher measurement accuracy. Abstract: Rotating structures are of interest in many engineering fields, where knowing their dynamic behaviour is important to prevent undesired operating states. However, the experimental measurement of vibrations in rotating structures is still a relatively demanding task that requires the use of special measurement technique or method. The paper deals with the application of high-speed digital image correlation in vibration analysis of rotating structures. The method introduced in this research is based on the elimination of rigid body motion components contained in the primary responses measured by cameras. The process of separation and subsequent elimination of these components is given by numerical post-processing of three-dimensional displacement fields. The basis is to determine rotation matrix and translation vector that optimally describe rigid transformation between two positions of an analysed object. The proposed method is applicable for measuring under both constant and variable speed of rotation. Practical application is presented by three experiments in which vibrations of a flat rotating disc were analysed. The first experiment is focused on determine the operating deflection shapes of the disc rotating at 4700 rpm. The second one is a run-up analysis under variable rotational speed that ranges from 0 to 4700 rpm. The aim of the third measurement is to obtain natural frequencies and modal shapes of the disc rotating at 4800 rpm. The results of the experiments show that the elimination of rigid body motions leads to a higher accuracy of measurement and provides more pronounced frequency response spectra.